Empowering posyandu cadres and mothers in monitoring under-five children’s development through education and simulation in Pinedapa Village - Sitorus, Sony Bernike Magdalena; Noya, Fransisca; Nurmalisa, Baiq Emy; Lailatul K, Marlina Fitria (Community Empowerment, 2025)
Developmental delays in under-five children are a global concern, with a prevalence of approximately 10% worldwide. In Central Sulawesi, the coverage of Early Stimulation, Detection, and Intervention for Growth and Development (SDIDTK) in toddlers remains low at 44.6%. Therefore, this community service activity aimed to enhance the knowledge and skills of posyandu cadres and mothers in Pinedapa Village in monitoring under-five children's development. The methods employed were education and simulation on monitoring child development. The results showed a significant increase in participants' knowledge; 80% of participants previously had poor knowledge, which increased to 100% having good knowledge post-education. Similarly, there was an improvement in participants' skills in monitoring under-five children's development after the simulation. This demonstrates the effectiveness of education and simulation in strengthening the capacity of partners, particularly concerning the monitoring of under-five children's development.